Images of the Church and the Christians' Imagination in Java - Tedjoworo, Hadrianus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2010)
We have reams of ideas about the church. We like to talk aboutthem, amazed by their resourcefullness. But these are ideas. When itis the ideas that are touched upon, the actors on the stage are not theordinary people. They are intellectuals; indeed, theologians. It is achurch-talk. However, when it comes down to the faithful, thechurch becomes churches. The ideas become images. The talkbecomes imagining. For Christians in Java, togetherness in thecircles of friends and families has always been an everydayness.And in this togetherness, what is spoken about is not the idea, butfirst of all the 'image' of a familial community. These people have alot of time to share how they can live their lives at each moment.They are not very much 'systematic' in their way of sharingexperiences, and they do not want to complicate things, for theyalready think that things have always been complicated enough inlife. Their simple hopes and concerns are always oriented towardsthe harmony of their community life. They imagine, interpret andevaluate many things, so as to find the relatedness of realities intheir togetherness. In this sense, this paper wants to capture thosemarvelous moments driven by the believers' imagination on the epistemological level of the believers' experience.